can school become a non-adultist institution? - liebel, manfred; meade, philip (childhood & philosophy, 2024)
To answer the question of whether school can become a non-adultist institution, this article examines the unequal adult–child (teacher–pupil) power relations that characterize school under the framework of bourgeois-capitalist society and that are upheld by certain functions, methods, norms and knowledge standards. Under the influence of the anti-authoritarian youth protest movements from the 1960s onwards, overt power in school (e.g. by means of corporal punishment) has been criticized and, in most countries, abolished. However, power imbalances between teachers and pupils have not disappeared, but rather developed towards a more subtle, covert power, e.g. by framing certain expectations. The hierarchical top-down and one-way learning principles of school institutions are mostly left uncontested. This article does not content itself with simply stating that schools repeatedly reproduce adultism under these societal conditions, but also discusses possible strategies and interventions that could shift unequal power relations and ultimately overturn them. It looks at various concepts and alternative forms of education critical of adultism that have emerged since the beginning of the 20th century both within and outside the state school system. It further explores the contradictions that should be expected to arise in their implementation within the framework of existing educational institutions. Particular attention is paid to the respective possibilities for action on the part of teachers and pupils. We offer a decisive challenge to teachers to rethink how they deal with their power, which is always derived and fragile, and how they can contribute to pupils empowering themselves and significantly influence learning and decision-making processes at school.